Acridinedione as selective flouride ion chemosensor: a detailed spectroscopic and quantum mechanical investigation. Issue 4 (9th January 2018) - Iqbal, Nafees; Ali, Syed Abid; Munir, Iqra; Khan, Saima; Ayub, Khurshid; al-Rashida, Mariya; Islam, Muhammad; Shafiq, Zahid; Ludwig, Ralf; Hameed, Abdul
Abstract : The use of small molecules as chemosensors for ion detection is rapidly gaining popularity by virtue of the advantages it offers over traditional ion sensing methods. Abstract : The use of small molecules as chemosensors for ion detection is rapidly gaining popularity by virtue of the advantages it offers over traditional ion sensing methods. Herein we have synthesized a series of acridine(1, 8)diones (7a–7l ) and explored them for their potential to act as chemosensors for the detection of various anions such as fluoride (F − ), acetate (OAc − ), bromide (Br − ), iodide (I − ), bisulfate (HSO4 − ), chlorate (ClO3 − ), perchlorate (ClO4 − ), cyanide (CN − ), and thiocyanate (SCN − ). Acridinediones were found to be highly selective chemosensors for fluoride ions only. To investigate in detail the mechanism of selective fluoride ion sensing, detailed spectroscopic studies were carried out using UV-visible, fluorescence and 1 H NMR spectroscopy. Fluoride mediated (NH) proton abstraction of acridinedione was found to be responsible for the observed selective fluoride ion sensing. Quantum mechanical computational studies, using time dependent density functional theory (TDDFT) were also carried out, whereupon comparison of acridinedione interaction with fluoride and acetate ions explained the acridinedione selectivity for the detection of fluoride anions. Our results provide ample evidence and rationale for further modulation and exploration of acridinediones as non-invasive chemosensors for fluoride ion detection in a variety of sample types.